2015
DOI: 10.1371/journal.pone.0124870
|View full text |Cite
|
Sign up to set email alerts
|

Serpine2/PN-1 Is Required for Proliferative Expansion of Pre-Neoplastic Lesions and Malignant Progression to Medulloblastoma

Abstract: BackgroundMedulloblastomas are malignant childhood brain tumors that arise due to the aberrant activity of developmental pathways during postnatal cerebellar development and in adult humans. Transcriptome analysis has identified four major medulloblastoma subgroups. One of them, the Sonic hedgehog (SHH) subgroup, is caused by aberrant Hedgehog signal transduction due to mutations in the Patched1 (PTCH1) receptor or downstream effectors. Mice carrying a Patched-1 null allele (Ptch1 ∆/+) are a good model to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…The downregulation of SERPINE2 may activate the Erk1/2 and P38 signaling pathways and lead to an increased invasion and metastasis of glioma cells, in which SERPINE2 seems to play a pro-tumor role (24). In another study, however, SERPINE2 may mediate an anti-tumor activity as its deficiency leads to the reduced proliferation of medulloblastoma cells (25). Our tissue microarray shows that SERPINE2 is expressed differentially in different types of brain tumors: abundant in oligodendroglioma and glioblastoma and extremely low in atypical meningioma and malignant ependymoma (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The downregulation of SERPINE2 may activate the Erk1/2 and P38 signaling pathways and lead to an increased invasion and metastasis of glioma cells, in which SERPINE2 seems to play a pro-tumor role (24). In another study, however, SERPINE2 may mediate an anti-tumor activity as its deficiency leads to the reduced proliferation of medulloblastoma cells (25). Our tissue microarray shows that SERPINE2 is expressed differentially in different types of brain tumors: abundant in oligodendroglioma and glioblastoma and extremely low in atypical meningioma and malignant ependymoma (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Pagliara showed that SERPINE2 affects glioma cell migration and invasiveness through the regulation of uPA and MMP-9/2 expression levels, contributing to the degradation of the ECM during tumor invasion (24). However, another study showed that SERPINE2 promoted pre-neoplastic lesion progression to the medulloblastoma owing to aberrant Hedgehog pathway activity independent of the SHH ligand (25).…”
Section: Introductionmentioning
confidence: 99%
“…Serpin E2 (Protease Nexin-1 (PN-1), belongs to the Serpin protein superfamily and acts as a protease inhibitor mainly for thrombin, plasmin and plasminogen activators, all factors associated with tissue remodeling. Although theoretically its ability to reduce proteolysis and extracellular matrix degradation would protect against cancer cell invasion and metastasis, serpinE2 overexpression leads to upregulation of matrix-metalloproteinase MMP9 which cleaves serpinE2 to allow protease mediated remodeling [33] . SerpinE2 is highly upregulated upon MAPK pathway stimulation, its overexpression is common in many cancers with such pathway oncogenic alterations [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Although theoretically its ability to reduce proteolysis and extracellular matrix degradation would protect against cancer cell invasion and metastasis, serpinE2 overexpression leads to upregulation of matrix-metalloproteinase MMP9 which cleaves serpinE2 to allow protease mediated remodeling [33] . SerpinE2 is highly upregulated upon MAPK pathway stimulation, its overexpression is common in many cancers with such pathway oncogenic alterations [33] . SOX10 is an essential factor for specification, survival and differentiation of neural crest derived lineages including melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular serine protease inhibitor (serpin) serpinE2, also known as PN-1, is overexpressed in various human cancers, including breast [2] and plays an essential role in malignant progression and metastasis [24]. However, the mechanism by which serpinE2 promotes metastasis in breast cancer models remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%